2022
DOI: 10.1002/1878-0261.13269
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy at the intersection of aging, senescence, and cancer

Abstract: Autophagy is an evolutionarily conserved cellular process in which macromolecules undergo lysosomal degradation. It fulfills essential roles in quality controlling cellular constituents and in energy homeostasis. Basal autophagy is also widely accepted to provide a protective role in aging and aging-related disorders, and its decline with age might precipitate the onset of a variety of diseases. In this review, we discuss the role of basal autophagy in maintaining homeostasis, in part through the maintenance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 167 publications
0
17
0
1
Order By: Relevance
“…In light of these functions, it is not surprising that autophagy has roles that protect against cancer. In the following subsections we first briefly summarize work on the roles of autophagy as a tumour suppressor mechanism that has been discussed in greater detail elsewhere [10][11][12][13][14] , to provide essential background understanding for our more detailed discussion of recent developments in the field.…”
Section: Suppression Of Tumour Developmentmentioning
confidence: 99%
“…In light of these functions, it is not surprising that autophagy has roles that protect against cancer. In the following subsections we first briefly summarize work on the roles of autophagy as a tumour suppressor mechanism that has been discussed in greater detail elsewhere [10][11][12][13][14] , to provide essential background understanding for our more detailed discussion of recent developments in the field.…”
Section: Suppression Of Tumour Developmentmentioning
confidence: 99%
“…The crosstalk between autophagy and endoplasmic reticulum stress is important in pulmonary fibrosis ( Ghavami et al, 2018 ; Maciel et al, 2018 ). Therapeutic approaches targeting autophagy have been shown to have great potential in cancer and aging ( Xia et al, 2021 ; Cassidy and Narita, 2022 ). Interestingly, studies have found that autophagy also plays an important role in IPF.…”
Section: Important Cells and Extracellular Matrix Involved In The Pat...mentioning
confidence: 99%
“…The role of autophagy in tumor development is complex and may depend on the stage and tissue of the tumor. Autophagy is thought to be essential for cell health, and its loss may lead to tumor damage (Cassidy & Narita, 2022). Natural products induce autophagy in NPC (Table 2).…”
Section: Regulation Of Autophagymentioning
confidence: 99%